Right of ship access to Port State under international law: all bark with no bite - Abdulkadir Owalabi, Abdulrazaq; Syed Abdul Kader, Sharifah Zubaidah (INSInet Publications, 2012)
By the International Maritime Organization regulations, foreign flagged vessels have the right to navigate waters and enter port states but the port states enjoy the power to set conditions for the accessibility of its ports. Sometimes, however, a memorandum of understanding between the state whose flag a ship is carrying and the port state is required before a foreign flagged vessel is able to navigate the waters and enter the port. The issue of access to ports of other states by foreign flagged vessels has been a subject of controversy among scholars. Although, the right of access is usually granted by treaty between the states concerned, the general view is that there is no such separate customary right. A more accepted view is that the states are entitled to prescribe and enforce circumstances for port entry. The paper takes into account the general principles of international law concerning foreign flagged vessels’ rights of access to port states. The paper concludes by arguing that the international instrument which grants the right of access to foreign flagged vessels is ineffective because port states grant access to foreign vessels that meet their conditions.